SARS-CoV-2 Infection of the Central Nervous System: A Case Report - Trifon Valkov; Radka Argirova; George Dimitrov (Viruses)
Central nervous system (CNS) infections caused by SARS-CoV-2 are uncommon. This case report describes the clinical progression of a 92-year-old female who developed a persistent neuroinfection associated with SARS-CoV-2. The patient initially presented with progressive fatigue, catarrhal symptoms, and a fever (38.6 °C). Initial laboratory findings revealed hypoxemia (O2 saturation 79.8%), acidosis (pH 7.3), an elevated C-reactive protein (CRP) level of 14.8 mg/L, and a high D-dimer level (2.15 µg/mL). Nasopharyngeal (NP) antigen and RT-PCR tests confirmed SARS-CoV-2 infection, and an NP swab also detected penicillin- and ampicillin-resistant Staphylococcus aureus. She was admitted for conservative management, including oxygen supplementation, IV fluids, and prophylactic anticoagulation. Subsequently, she developed neurological symptoms—lethargy, discoordination, and impaired communication—without signs of meningism. Cerebrospinal fluid (CSF) analysis identified SARS-CoV-2 RNA (Ct = 29) on RT-PCR, while bacterial cultures remained negative. Treatment was intensified to include 10% mannitol, dexamethasone, and empiric ceftriaxone. Despite these interventions, the patient remained somnolent, with a Glasgow Coma Scale (GCS) score of 10. Upon discharge, her GCS had improved to 14; however, she continued to experience lethargy and cognitive issues, commonly described as “brain fog”. Inflammatory markers remained elevated (CRP 23 mg/L) and repeat RT-PCR of CSF confirmed a persistent SARS-CoV-2 presence (Ct = 31). This case underscores the potential for SARS-CoV-2 to cause prolonged CNS involvement, leading to persistent neurological impairment despite standard therapy. Further research is essential to clarify the pathophysiology of and determine optimal management for SARS-CoV-2 neuroinfections.